Determination of Directions to Increase the Efficiency of Municipal Budget Funds Spending - E. V. Orlov; V. A. Kosareva; E. S. Smirnova (Управленческое консультирование)
The article deals with the issue of increasing the efficiency of spending local budgets. Such a study is relevant in modern conditions, when the own budget revenues of the vast majority of municipalities do not cover the costs, and many local budgets receive more than half of the funds from higher budgets. Given the difficult socio-economic situation that has developed in recent years, the search for tools, methods and directions for optimizing local budget expenditures is becoming a priority.The purpose of the study is to determine the areas of spending budget funds, measures aimed at optimizing which could bring the greatest effect. The result of the work was the identification of the most “typical” (classical) municipalities (in the context of each of their main types), the structure of expenditures of which is similar to the average structure of municipal budgets, determined on the basis of an analysis of the entire sample. Based on the subsequent analysis, the main elements of the budget costs were identified, the work on which could bring the greatest savings. All this is supplemented by optimization measures and proposals for the main areas of spending, determined on the basis of the results of scientific literature analysis, the use of which will significantly increase the efficiency of budget expenditures.